A rule of hydrological regulating on nutritional status of Poyang Lake, since the operation of the Three Gorges Dam. (September 2019) - Ding, Yuekui; Wang, Shengrui; Zhang, Wenqiang; Feng, Minglei; Yu, Ruihong
Highlights: A regulating rule on nutritional status of Poyang Lake was excavated. Hydrological regulation kept the nutritional equilibrium of Poyang Lake. Storage change and accompanying nutrient inputs affected lake nutritional status. This rule could be used to manage the nutritional status of Poyang Lake. Abstract: Anthropogenic activities have aggravated nutritional status of lakes. Hydrological regime of Poyang Lake has been altered since the operation of the Three Gorges Dam (TGD). Will this further affect the nutritional status of Poyang Lake? We studied the dynamic changes of the nutritional status of Poyang Lake between 2003 and 2015 under this new hydrological regime. A regulating rule of hydrological regime on lake nutritional status was found, in which change in water storage and accompanying nutrient input acted as the dominant influencing factors. The rule was represented as a fitting function of the ratio of change in storage (Δ Q, Δ Q = Qoutflow − Qinflow ) to nutrient input (TN − TP)input ) and the nitrogen and phosphorus concentration in the lake water. The specific functional formulas were as follows: y1 = 148.32x 2 − 362.51x + 229.83 (R 2 = 0.8771, lower boundary) and y2 = −74.92x 2 + 135.25x − 17.139 (R 2 = 0.9049, upper boundary) for TN; y1 ′ = 94009x 2 − 24302x + 1345 (R 2 = 0.9729, lower boundary) and y2 ′ = −68439x 2 + 7588x + 514.42 (R 2 = 0.8588, upper boundary) for TP. In the lake management, the hydrological regulating of the upper boundary and the lower boundary should be expressed as: the range ofΔ Q/TNinput was 8.22–43.07 and 8.35–35.06 respectively, similarly, 316.64–723.98 and (−218.37)−523.33 ofΔ Q/TPinput range. This rule applied to the following scenarios: concentrations of TN and TP were below 1.60 mg L −1 and 0.133 mg L −1, and continue to increase over a 4–5 years. This study provided a key practical reference for the management of dam-impact lakes worldwide.